Comparison of Goldmann Applanation, Diaton Transpalpebral and Air Puff Tonometers - Abdul Hannan, Sana Nadeem, B. A. Naeem, Rabeea Tahira, Shizza Khalid (Pakistan Journal of Ophthalmology, 2015)
Purpose: To compare the intraocular pressure (IOP)) measurements in normal subjects, between the newly developed, Transpalpebral tonometer (Diaton®), Goldmann Applanation tonometer (GAT), and Air-puff Tonometer (APT), and to assess agreement between the three devices. Material and Methods: A total of 400 eyes of 200 random subjects were included in this cross-sectional, comparative study. IOP was measured with APT (Canon Full Auto Tonometer TX-F®), followed by Diaton®, and lastly GAT (Haag Streit AT 900® tonometer) in both eyes. The mean IOPs and the differences between IOPs of the tonometers were calculated by the paired t-tests. Their correlations were calculated using the Pearson correlation coefficients, mean differences were analyzed by one-way analysis of variance, and agreement was analyzed by the Bland-Altman method. Results: The mean IOPs noted for Diaton, GAT, and APT were 14.78 ± 3.22, 14.62 ± 3.01, and 14.42 ± 3.22 mm of Hg, respectively. The Pearson’s correlation coefficient (r) between Diaton and GAT was 0.314, between Diaton and APT; 0.334, and between GAT and APT; was 0.745. Hence, the strongest correlation was between GAT and APT, followed by moderate correlation of Diaton with APT, and least between Diaton and GAT. However, correlations between all three tonometers were significant at the 0.01 level. Bland- Altman analysis revealed that the mean differencesbetween Diaton and GAT measurements was 0.16 ± 3.6 mm Hg, between GAT and APT was 0.20 ± 2.2 mm Hg, and between Diaton and APT was 0.36 ± 3.7 mm Hg. The 95 % limits of agreement were smallest between GAT and APT, as compared to the other two pairs. Thus good agreement was observed between GAT and APT, and there was fair agreement of Diaton with both GAT and APT. Conclusion: Measurement of intraocular pressures by all three tonometers was comparable with good correlation in normal adults. There was good agreement between GAT and APT, and fair agreement of Diaton with GAT and APT. APT can be used as a screening device for patients. However, Diaton is not a very useful device for screening purpose, because of wider variations. Key words: Intraocular pressure, Transpalpebral tonometry, Goldmann Applanation tonometer, Air-puff tonometry.